Development of Kucermat Media for Early Writing Skill Children Aged 5-6 Years - Yuni Dwi Suryani; Nurbiana Dhieni; Sri Wulan (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
Early writing is one of the needs needed in preparation for elementary school. Research and development carried out to develop learning media to improve the readiness of early writing for children 5-6 years in the city of Palembang. KUCERMAT media development is based on needs analysis. KUCERMAT media development uses the ADDIE model (analysis, design, development, implementation, and evaluation). KUCERMAT Trial Media was carried out with a pre-experimental experimental method with a one-group pretest-posttest design. The number of respondents in the KUCERMAT media trial were 25 children. The results of the analysis of the difference in the total average of the pretest and posttest showed an increase in children's early writing by 22.81%. Then the statistical analysis of paired sample t-tests was calculated by using the IBM SPSS Statistics 22 obtained t count value of 17.777 with a significance value (2-tailed) of 0,000 to 0,000 <0.05. While the ttable value of 2.06 with n-1 = 24. Thus tcount> ttable so that it can be used to improve the KUCERMAT media effectively used to improve the readiness of early writing in children aged 5-6 years.Keywords: Writing readiness, Kindergarten, KUCERMAT Media AbstrakKesiapan menulis merupakan salah satu kemampuan yang dibutuhkan sebagai dasar persiapan menuju ke sekolah dasar. Penelitian dan pengembangan yang dilaksanakan bertujuan mengembangkan media pembelajaran untuk meningkatkan kesiapan menulis permulaan anak 5-6 tahun di Kota Palembang.  Pengembangan media KUCERMAT dilakukan berdasarkan analisis kebutuhan. Pengembangan media KUCERMAT menggunakan model ADDIE (analysis, design, development, implement, dan evaluate). Uji efektivitas media KUCERMAT dilakukan dengan metode eksperimen pre-experimental dengan desain one-group pretest-posttest. Jumlah respoden pada uji efektivitas media KUCERMAT sebanyak 25 anak. Hasil analisis perbedaan total rata-rata dari pretest dan posttest menunjukkan terjadi peningkatan menulis permulaan anak sebesar 22,81%. Kemudian analisis statistik paired sample t-test dihitung dengan aplikasi IBM SPSS Statistik 22 memperoleh nilai t hitung sebesar 17,774 dengan nilai signifikansi (2-tailed) sebesar 0,000 sehingga 0,000<0,05. Sedangkan nilai ttabel sebesar 2,06 dengan n-1=24.  Dengan demikian thitung>ttabel sehingga dapat disimpulkan bahwa penggunaan media KUCERMAT efektif digunakan untuk meningkatkan kesiapan menulis permulaan pada anak usia 5-6 tahun.Kata Kunci: Kesiapan menulis permulaan, TK B, Media KUCERMAT